2009
DOI: 10.1007/s10531-009-9612-8
|View full text |Cite
|
Sign up to set email alerts
|

Community based natural resource management in Zimbabwe: the experience of CAMPFIRE

Abstract: Communal Areas Management Programme for Indigenous Resources (CAMPFIRE) is a long-term programmatic approach to rural development that uses wildlife and other natural resources as a mechanism for promoting devolved rural institutions and improved governance and livelihoods. The cornerstone of CAMPFIRE is the right to manage, use, dispose of, and benefit from these resources. Between 1989 and 2006, CAMPFIRE income, mostly from high valued safari hunting, totalled nearly USD$ 30 million, of which 52% was allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 3 publications
2
71
0
1
Order By: Relevance
“…However, legally, the lowest formal institution in communal lands was the Rural District Council (RDC), formed through the Local Government Act. To bridge this gap between policy, intent of wildlife officials, and the existing organizational structure of the Ministry of Local Government and Rural Development, a strategic compromise was reached and Appropriate Authority was devolved to District Councils with a gentleman's agreement that this be further devolved to wildlife "producer communities" (Taylor, 2009;Campbell et al, 2001;B. Child, 1996a) .…”
Section: History Of the Campfire Programmentioning
confidence: 99%
See 1 more Smart Citation
“…However, legally, the lowest formal institution in communal lands was the Rural District Council (RDC), formed through the Local Government Act. To bridge this gap between policy, intent of wildlife officials, and the existing organizational structure of the Ministry of Local Government and Rural Development, a strategic compromise was reached and Appropriate Authority was devolved to District Councils with a gentleman's agreement that this be further devolved to wildlife "producer communities" (Taylor, 2009;Campbell et al, 2001;B. Child, 1996a) .…”
Section: History Of the Campfire Programmentioning
confidence: 99%
“…high wildlife populations, increased income to community, and relatively high number of community funded projects) (N. Nabane and Matzke, 1997;Matzke and Nabane, 1996). The retrospective opinions of people interviewed between 2007 and 2009 (Taylor and Murphree, 2007a;Taylor, 2009) also indicated that Masoka was a successful Communal Areas Management Program for Indigenous Resources (CAMPFIRE) project managed through an impersonal and institutionalized governance system that delivered development and cash benefits to its members (Murombedzi, 1997;Taylor, 2007). However, between 2009 and 2011 it lost its impersonal and institutionalized rule as the elite centralized the governance of CAMPFIRE benefits.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Cantarello et al (2014) and , this could potentially be achieved by adopting a participatory forest management approach, where local people are actively involved in forestry activities. In recent years, there has been increasing interest in such participatory approaches in many countries, illustrated by the CAMPFIRE project in Zimbabwe (Taylor 2009) and the development of Community Forest User Groups in Nepal (Lawrence et al 2006). In order to introduce such approaches to Kyrgyzstan, such approaches will need to be adapted to the prevailing pattern of land ownership.…”
mentioning
confidence: 99%
“…An interesting experience has taken place in the Communal Areas Programme for Indigenous Resources (CAMPFIRE) in Zimbabwe, i.e., the flagship community-based resource program in southern Africa, where the legally mandated authority responsible for wildlife management in the country has decentralized state authority and conferred privileges on occupiers of titled land as custodians of wildlife, fish, and plants. Hence, land occupiers were given de facto responsibility for wildlife and were made beneficiaries of sound wildlife conservation and use (Taylor, 2009 …”
Section: Land Insecuritymentioning
confidence: 99%